(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Chronic spontaneous urticaria is a chronic skin disease with significant impairment of quality of life. A significant association with psychiatric co-morbidities has been shown in recent studies. To evaluate this association, we conducted a cross-sectional study where the first phase include assessment for psychiatric co-morbidities with 12-item general health questionnaire (GHQ-12). In the second phase, patients with GHQ-12 ≥3 were assessed for various psychiatric illnesses using Hamilton anxiety rating scale, Beck depression inventory, and Yale-Brown obsessive compulsive scale. Clinical diagnosis was made using ICD-10 criteria and quality of life was measured using WHO-QOL brief scale. A total of 108 patients were recruited, 22 (18.5%) of them had GHQ-12 ≥3 and were included in second phase. On phase 2 screening, 8 (7.4%) patients had anxiety and 12 (11.1%) patients had depression. Significant impairment of quality of life affecting all 4 domains was seen in all the patients. Our study shows a high incidence of psychiatric co-morbidities (18.5%) especially anxiety and depression in patients with chronic spontaneous urticaria.